A Cost Analysis of Cardiac Magnetic Resonance Imaging in the Diagnostic Pathway of Patients Presenting With Unexplained Acute Myocardial Injury and Culprit-Free Coronary Angiography - Murphy, Theodore; Jones, Daniel A.; Friebel, Rocco; Uchegbu, Ijeoma; Mohiddin, Saidi A.; Petersen, Steffen E. (Frontiers in Cardiovascular Medicine, 2021)
Aims: To determine financial implications of implementing cardiac magnetic resonance imaging (CMR) in the diagnostic pathway of a population with unexplained acute myocardial injury and normal coronary angiography. Methods and results: We performed a focused cost-benefit analysis using a hypothetical population of 2,000 patients with unexplained acute myocardial injury and normal coronary angiography divided into two groups to receive either standard or CMR guided management over a ten-year period. As healthcare practice and costs considerably vary geographically and over time, an algorithm with 15 key variables was developed to permit user-defined calculations of cost-benefit and other analyses. Using current UK costs, routine use of CMR increases healthcare spending by 14% per patient in the first year. After 7 years, CMR guided practice is cost neutral, reducing cost by 3% per patient 10 years following presentation. In addition, CMR -guided therapy results in 7 fewer myocardial infarctions and 14 fewer major bleeding events per 1000 patients over a ten-year period. The three most sensitive variables were, in decreasing order, the cost of CMR, the cost of Ticagrelor and the percentage of the population with a myocardial infarction requiring dual anti-platelet therapy. Conclusion: Routine use of CMR in patients with unexplained acute myocardial injury and normal coronary angiography is associated with cost reductions in the medium to long term. The initial higher cost of CMR is offset over time and delivers a more personalized and higher quality of care.